Capital Intentions : Female Proprietors in San Francisco, 1850-1920 - Sparks, Edith (Book collections on Project MUSE., 2006)
Late nineteenth-century San Francisco was an ethnically diverse but male-dominated society bustling from a rowdy gold rush, recovery from the earthquake, and explosive economic growth. Within this booming marketplace, some women stepped beyond their roles as wives, caregivers, and homemakers to start businesses that combined family concerns with money-making activities. Edith Sparks traces the experiences of these women entrepreneurs, exploring who they were, why they started businesses, how they attracted customers and managed finances, and how they dealt with failure.